Analysis of the spatial skills of the degree student in engineering: A gender approach - Recalde, Irantzu; Ferrández, Daniel; Yedra, Engerst; Zaragoza, Alicia (Advances in Building Education, 2022)
The objective of this work is to carry out an approach to the study of spatial skills by gender in engineering students. For this, the analysis of a test consisting of 12 questions was carried out on a sample of 220 students from the Universidad Politécnica de Madrid, of which 134 were male and 81 were female. The study evaluated three different types of spatial skills such as relation, rotation, and visualization. From the analysis of the results obtained in the sample, it appears that in engineering degree courses the difference between men and women in terms of spatial ability is not significant, with other variables such as the university degree carried out by the sample showing a greater statistical association.